2018
DOI: 10.1016/j.energy.2018.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Linking design and operation performance analysis through model calibration: Parametric assessment on a Passive House building

Abstract: 10 Efficient buildings are an essential component of sustainability and energy transitions, 11 which represent today a techno-economic and socio-economic problem. New paradigms 12 are emerging both for new and existing buildings (e.g. NZEBs) and passive design 13 strategies are becoming increasingly common. However, the adoption of these strategies 14 in mild climates has to be carefully evaluated to prevent overheating in intermediate 15 seasons and increasing cooling loads in summer, considering also climate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 65 publications
0
30
0
Order By: Relevance
“…Various researchers have demonstrated that occupants affect the building energy consumption the most, and they are also the primary cause of the "Energy-performance Gap" [5][6][7][8]. Several previous studies have investigated the variation in energy consumption as a function of the actual occupant characteristics and activities.…”
Section: Effects Of Occupant Characteristics On Energy Consumptionmentioning
confidence: 99%
“…Various researchers have demonstrated that occupants affect the building energy consumption the most, and they are also the primary cause of the "Energy-performance Gap" [5][6][7][8]. Several previous studies have investigated the variation in energy consumption as a function of the actual occupant characteristics and activities.…”
Section: Effects Of Occupant Characteristics On Energy Consumptionmentioning
confidence: 99%
“…In general, the U-value of building materials was treated as a categorical variable because it is a set value that does not vary over time. Based on these results, we concluded that the electricity of a building can be effectively managed if only four or five major energy variables derived from the building are controlled or used as key points of operation [53,54]. consumption.…”
Section: Research Resultsmentioning
confidence: 95%
“…As a matter of fact, buildings are not only electricity consumers but also thermal energy ones. Coupling electrification and energy refurbishment, the actual integration of solar energy must be ensured from the pre-design to the operation phase [25]. Therefore, modelling and optimization should aim at cost-benefit analysis for renovation [26], together with the integration of Information & Communication Technologies (ICT) such as building automation [27].…”
Section: Introductionmentioning
confidence: 99%